PERANCANGAN DESAIN ALAT PEMBAKARAN SAMPAH RAMAH LINGKUNGAN - Purnama, Mochamad Iqbal; Saleh, Agus (Motor Bakar : Jurnal Teknik Mesin, 2025)
AbstractIn designing an environmentally friendly waste incineration device, it is important to consider the product life cycle comprehensively. This includes selecting environmentally friendly construction materials, such as recycled or biodegradable materials, as well as designing for ease of maintenance and upkeep to extend the lifespan of the device. Additionally, modular and adaptable design can allow for adaptation to different local needs and conditions. Environmentally friendly waste incineration device design should consider technical and practical concepts that can reduce negative impacts on the environment and human health. One key aspect is combustion efficiency, which can be achieved through the selection of advanced combustion technologies and proper control of temperature and airflow. Furthermore, reducing pollutant emissions such as hazardous particles, greenhouse gases, and toxic compounds should be a primary focus. This can be accomplished using effective exhaust gas filtration and purification technologies. In designing this device, it is important to consider social and economic aspects, including technology availability and accessibility, as well as operational and maintenance costs.Keyword : Incinerator, Wate Incinerator, Environmentally Friendly.